Связь ПЦС-векторов с кристалломорфологией берилла из камерных пегматитов Волыни (Украина) - Вовк, Олександр Павлович; Наумко Игорь Михайлович; Vovk, Oleksandr P.; Naumko, Ihor M. (Издательство «Hаука», Санкт-Петербургское отделение, 2014)
Приводится краткий обзор структурных подходов для определения морфологически важных форм на кристалах берилла. Показаны результаты анализа кристаллической структуры берилла. Определены ПЦС-векторы и F-, S-, К-грани по П. Харману и В. Г. Пердоку. Рассчитана величина dhkl и определены истинные F-грани. Полученные результаты сравниваются с равновесной формой кристалла по методу Доннея-Харкера и морфологической важностью простых форм, согласно их симметрии, по И. И. Шафрановскому. Проводится сопоставление теоретических расчетов с морфологией берилла из камерных пегматитов Волыни.

Review of structural approach allows determining the morphologically important forms on beryl crystals. Analysis of the beryl crystalline structure has revealed PBC-vectors and F-, S-, K-faces, according to P. Hartman and W.G.Perdok. Values of d hkl were calculated, and genuine F-faces have been determined. Obtained results are compared with the equilibrium shape of the crystal, according to the Donney-Harker method, and the morphological importance of simple forms, according to their symmetry, after I.I.Shafranovsky. The theoretical calculations are compared with the real morphology of beryl from Volyn chamber pegmatites.
INFLUENCE OF PBC-VECTORS ON THE CRYSTAL MORPHOLOGY OF BERYL FROM VOLYN CHAMBER PEGMATITES (UKRAINE)
Keywords: берилл; кристалломорфология; ПЦС-векторы; камерные пегматиты; Beryl; chamber pegmatites; Volyn; crystal morphology; PBC-vectors